2017
DOI: 10.1093/pcp/pcx110
|View full text |Cite
|
Sign up to set email alerts
|

FLUCTUATING-LIGHT-ACCLIMATION PROTEIN1, Conserved in Oxygenic Phototrophs, Regulates H+ Homeostasis and Non-Photochemical Quenching in Chloroplasts

Abstract: Plants have mechanisms allowing them to acclimate to intense light conditions, which involves the dissipation of excess light energy. These mechanisms allow plants to perform photosynthesis efficiently and, therefore, must be accurately and precisely controlled. However, how plants dissipate excess light energy has yet to be fully elucidated. Herein we report the identification of a gene, which we named Fluctuating-Light-Acclimation Protein1 (FLAP1), that is conserved in oxygenic phototrophs. We show that Arab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 40 publications
2
33
0
Order By: Relevance
“…Far‐red light increased the photoprotection of PSI against fluctuating light possibly due to the beneficial effects of far‐red light on photosynthesis thereby accelerating NPQ relaxation and PSII yield (Kono, Yamori, Suzuki, & Terashima, 2017). In a recent study, a FLUCTUATING LICHT ACCLIMATION PROTEIN1 (FLAP1) was identified controlling NPQ formation during fluctuating light (Sato et al, 2017).…”
Section: Light As a Stressormentioning
confidence: 99%
“…Far‐red light increased the photoprotection of PSI against fluctuating light possibly due to the beneficial effects of far‐red light on photosynthesis thereby accelerating NPQ relaxation and PSII yield (Kono, Yamori, Suzuki, & Terashima, 2017). In a recent study, a FLUCTUATING LICHT ACCLIMATION PROTEIN1 (FLAP1) was identified controlling NPQ formation during fluctuating light (Sato et al, 2017).…”
Section: Light As a Stressormentioning
confidence: 99%
“…Although the mechanisms of qE induction are well understood, the detailed mechanisms by which the lumen pH is appropriately adjusted according to light intensity have yet to be elucidated. We recently screened for Arabidopsis genes that are co-expressed with NPQ-related genes that are specifically conserved in oxygenic phototrophs; we identified a gene that encodes an uncharacterized NPQ-regulatory protein, which we named Fluctuating-Light Acclimation Protein1 (FLAP1) (Sato et al, 2017). The Arabidopsis flap1 mutant has a larger NPQ value than does the wild type (WT) and has a pale-green leaf phenotype, but only when grown under light of fluctuating intensity (fluctuating light) (Sato et al, 2017;Trinh et al, 2019), indicating that FLAP1 helps plants acclimate to fluctuating light.…”
Section: Introductionmentioning
confidence: 99%
“…This might be due to the beneficial effects of FR light on photosynthesis thereby accelerating NPQ relaxation and PSII yield (Kono et al, 2017). In a recent study, a FLUCTUATING-LIGHT-ACCLIMATION PROTEIN1 (FLAP1) was identified probably controlling NPQ formation during FL (Sato et al, 2017).…”
Section: Stress Caused By Fluctuating Lightmentioning
confidence: 99%